2019
DOI: 10.1039/c9tc00979e
|View full text |Cite
|
Sign up to set email alerts
|

Layered manganese bismuth tellurides with GeBi4Te7- and GeBi6Te10-type structures: towards multifunctional materials

Abstract: Non-stoichiometry is the key to single-phase layered compounds in the system Mn/Bi/Te, which is essential to evaluate their multifunctional properties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 68 publications
(74 reference statements)
7
39
0
Order By: Relevance
“…Table 1 also shows that defect densities and the Mn deficiency increases from MnBi 2 Te 4 to MnBi 4 Te 7 , consistent with the trend observed experimentally. [ 5f,7b,15 ] Based on calculated formation energies of MnBi on different sites in MnBi 4 Te 7 , it can be shown that, under thermal equilibrium, about 5/6 of MnBi are located in the QL while the other 1/6 are in the SL.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 also shows that defect densities and the Mn deficiency increases from MnBi 2 Te 4 to MnBi 4 Te 7 , consistent with the trend observed experimentally. [ 5f,7b,15 ] Based on calculated formation energies of MnBi on different sites in MnBi 4 Te 7 , it can be shown that, under thermal equilibrium, about 5/6 of MnBi are located in the QL while the other 1/6 are in the SL.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous experiments showed an increased Mn deficiency in MnBi 6 Te 10 . [ 7b,15 ] The strain‐induced antisite formation as discussed above may also explain the observation of a few percent of Te Se and Se Te antisites in the topological insulator Bi 2 Te 2 Se, which has an ordered crystal structure with the small‐sized Se occupies the middle layer of a QL. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations